Let the Little Children Come to Me - Miguel Portela; Paul Schweinzer (Center for Economic Studies and ifo Institute (CESifo), 2018)
We document the relationship of a set of individual choices - including parenthood, marital state, and income - with an individual's cause of death. Using the data set of the Office for National Statistics Longitudinal Study (ONS-LS) which follows one percent of the population of England and Wales along five census waves 1971, 1981, 1991, 2001, and 2011, our competing risks analysis yields several striking results. 1) Females have only a 28% chance to die of cancer when they have children (compared to childless females); 2) males have a 71% increased chance of dying from cancer when they are married (compared to unmarried males); 3) females with children have only a 34% risk to die of heart disease and 4) a 53% chance of dying from infections (compared to females without children); 5) married men have an increased expectation of 23% to die of heart disease (compared to unmarried men); 6) high income and house ownership always is associated with higher survival but less so than having children.
Keywords: I10; J10; 330; children; mortality. longevity